Honorary Doctor of Laws Degree for Madeline Parent - Sangster, Joan (Labour / Le Travail, 2000)
On 4 June 1999, Madeline Parent was awarded an honorary doctorate at Trent University in recognition of her outstanding work in the trade union and feminist movements. Joan Sangster, Chair of Women's Studies, introduces Parent and offers a tribute to her historic contributions to improving the lives of workers and women in Canada.